Managing bile duct injuries sustained during cholecystectomies - Srivastava, Vijay Prakash; Agarwal, Shwetank; Agarwal, Ajai; Sharan, Jagadamba (International Surgery Journal, 2017)
Background: Medical science is a blend of Art and Science. Technology evolved conceived presumably to improve the medical science. Increasing incidence of bile duct injury during laparoscopic cholecystectomies proved otherwise. Multiple factors e.g. cognitive psychology, laparoscopic environment and no proper algorithms to manage, factor may be responsible for these results. To understand properly the mystique, we under took this study. Methods: This study was conducted on 200 cases which underwent laparoscopic cholecystectomies. 12 cases developed bile duct injury during laparoscopic cholecystectomies and 10 cases of bile duct injury sustained through open cholecystectomies were studied in detail results noted and analyzed. Results: All these cases 12/200 laparoscopic cholecystectomy, 10/200 open cholecystectomies were followed up, sign and symptoms noted, USG studies, ERCP stenting, sphincterotomy studies reviewed and sequence of management underlined. Conclusions: Early realisation of bile duct injuries remains the hall mark of she success. Even in cases detected late, conservative procedure and stenting with or without sphincterotomy given relief in number of cases. Finally, if surgery is contemplated Roux-Y-biliary enteric procedure gives much better results.